EVALUASI PROGRAM PENYULUHAN PERTANIAN BERBASIS KOMODITAS UNGGULAN DI WILAYAH BINAAN UPTD BPP KOTA PALEMBANG - Namira Salsabila; Oktarina, Selly; Adi Suryadi (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2026)
This study aims to evaluate the agricultural extension program based on superior commodities implemented by the UPTD BPP of the Food Security and Agriculture Office of Palembang City. The research location includes several areas under the guidance of the Agricultural Extension Center (BPP) in Palembang City, namely BPP Gandus, BPP Seberang Ulu, BPP Talang Betutu, and BPP Sekojo. The methods used were field observations, interviews, and primary and secondary data collection from farmers and agricultural extension officers. The results showed that extension programs based on superior commodities, especially rice and horticulture, had a positive impact on increasing farmers' knowledge by 70%. However, there are some constraints, such as limited access to technology and differences in environmental conditions between regions. This evaluation indicates that this extension program can increase agricultural productivity in Palembang City, but needs to be improved in terms of supporting infrastructure and access to technology.